2019
DOI: 10.1136/annrheumdis-2018-214971
|View full text |Cite
|
Sign up to set email alerts
|

Are corticosteroid injections needed after needling and lavage of calcific tendinitis? Randomised, double-blind, non-inferiority trial

Abstract: ObjectiveSteroid injections are common after an ultrasound-guided puncture and lavage (UGPL) of calcific tendonitis of the rotator cuff. However, steroids may prevent calcification resorption and negatively affect tendon healing. Our study was designed to determine whether saline solution was non-inferior to steroids in the prevention of acute pain reactions in the week following UGPL.MethodsThis was a randomised, double-blinded, controlled non-inferiority trial with 12-month follow-up. We included 132 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
0
19
0
2
Order By: Relevance
“…First, conventional NACD+ corticosteroids was compared with NACD + PRP, but there was no placebo control group to evaluate the additive use of corticosteroids or PRP or even the effect on NACD as such. However, a recent study by Darrieutort-Laffite et al 6 compared NACD+ corticosteroids to NACD without corticosteroids. The results of their study demonstrated that NACD+corticosteroids was superior to NACD without corticosteroids in decreasing pain and disability in the short term without any effect on the rate of resorption of calcific deposits.…”
Section: Discussionmentioning
confidence: 99%
“…First, conventional NACD+ corticosteroids was compared with NACD + PRP, but there was no placebo control group to evaluate the additive use of corticosteroids or PRP or even the effect on NACD as such. However, a recent study by Darrieutort-Laffite et al 6 compared NACD+ corticosteroids to NACD without corticosteroids. The results of their study demonstrated that NACD+corticosteroids was superior to NACD without corticosteroids in decreasing pain and disability in the short term without any effect on the rate of resorption of calcific deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, acute spontaneous resorption of calcific tendinitis was associated with migration of the calcium into the SAB, leading to rapid but painful disappearance of the calcic deposit. 7 UGPL should mimic this mechanism and create a path for the calcium to migrate from the tendon to the bursal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,19,23 Finally, we and others have found that steroid injections performed after the procedure significantly decreased pain and improved function in the short term but had no added value after 3 months. 7,25 While clinical improvement and the disappearance of calcification are obtained in most patients, some will not improve or will experience a delay in this clinical improvement. Several studies have found an association between persistence of calcification and worse outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are many ways to treat CT, and each treatment has its own advantages and disadvantages [7,[35][36][37]. In a recent systematic and network meta-analysis, Wu al.…”
Section: Discussionmentioning
confidence: 99%